Taxonomic study of the Cobitis striata complex (Cypriniformes, Cobitidae) in Japan - Nakajima, Jun (Zootaxa, 2012)
Three new species and six new subspecies of the genus Cobitis from the western part of the Japanese archipelago aredescribed: Cobitis kaibarai sp. nov., Cobitis magnostriata sp. nov., Cobitis minamorii sp. nov., Cobitis striata fuchigamiisubsp. nov., Cobitis striata hakataensis subsp. nov., Cobitis minamorii oumiensis subsp. nov., Cobitis minamoriitokaiensis subsp. nov., Cobitis minamorii saninensis subsp. nov., and Cobitis minamorii yodoensis subsp. nov. Cobitisstriata Ikeda, 1936 was redescribed on the basis of specimens collected from the type locality. The four striated spinedloaches, C. striata, C. kaibarai, C. magnostriata, and C. minamorii were clearly distinguished by the pelvic myotomenumber, shape of the lamina circularis, black spots at the caudal base, body shape, and egg diameter. Although thesesubspecies of C. striata and C. minamorii are remarkably alike in morphology, the adult males of the subspecies had different longitudinal patterns of pigmentation during the non-spawning season.